Associations between maternal overweight/obesity during pregnancy and body composition in young adult offspring - Rerkasem, Amaraporn; Lyons-Reid, Jaz; Namwongprom, Sirianong; Wongsrithep, Suthathip; Mangklabruks, Ampica; Phirom, Kochaphan; Rerkasem, Kittipan; Derraik, José G. B. (Frontiers in Public Health, 2024)
Background Maternal obesity is associated with an increased risk of large-for-gestational-age births and childhood obesity. However, evidence on its potential associations with long-term offspring body composition remains limited. This prospective cohort study examined associations between maternal body mass index (BMI) during pregnancy and body composition in the young adult offspring. Methods Participants were the offspring from a birth cohort in Chiang Mai (Thailand). Maternal BMI was assessed at the first antenatal clinic visit (≤24 weeks of gestation) in 1989–1990. In 2010–2011, we followed up the offspring at approximately 20 years of age, assessing their body composition using whole-body dual-energy X-ray absorptiometry (DXA) scans. Associations between maternal BMI and offspring body composition were explored using unadjusted and adjusted analyses. Results We assessed 391 young adults (55% were females). Higher maternal BMI was associated with increased offspring fat mass and lean mass. In adjusted analyses, offspring of mothers with overweight/obesity exhibited total body fat percentages 1.5 (95% CI 0.1, 2.9; p = 0.032) and 2.3 (95% CI 0.2, 4.5; p = 0.036) percentage points higher than offspring of normal-weight and underweight mothers, respectively. Fat mass index was similarly higher: 0.9 kg/m2 (95% CI 0.3, 1.5 kg/m2; p = 0.002) and 1.4 kg/m2 (95% CI 0.5, 2.3 kg/m2; p = 0.002), respectively. However, no differences in visceral adiposity were detected. Conclusion Higher maternal BMI during pregnancy was associated with increased adiposity in young adult offspring. Our findings suggest that the cross-generational transmission of maternal obesity-related traits is associated with increased offspring adiposity in the long term.